Pengembangan Desain Wizer.Me Sebagai E-LKPD pada Mata Pelajaran Matematika Materi Bilangan Bulat Kelas VII SMP - Yunita, Rini; Rosmaria, Rosmaria; Novrianti, Novrianti; Masnur, Alkadri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The development of E-LKPD in Grade VII Mathematics Subject of SMPN 5 Linggo Sari Baganti is motivated by a teacher-oriented learning pattern, as well as limitations in the use of digital teaching materials such as E-LKPD. This research aims to produce valid and practical E-LKPD products so that they can be used in the learning process. The type of research used is Research and Development (R&D). The development model used in this study is a 4D model. The 4D model consists of 4 stages, namely define, design, develop and disseminate. The results of the development of E-LKPD were obtained through validity and practicality tests. The product validity test was validated by three validators consisting of one material validator, namely a teacher of Mathematics Class VII SMPN 5 Sari Baganti and two media validators, namely lecturers from the Department of Curriculum and Educational Technology, Padang State University. The product practicality test was carried out by conducting an E-LKPD trial for grade VIIB students of SMPN 5 Linggo Sari Baganti. The results of the validity test by a material expert and two media experts obtained an average score of 4.86, 4.86, and 4.8 respectively which was categorized as